Pemberdayaan Perempuan Melalui UMKM Mekarsari Di Kelurahan Kandri Kecamatan Gunungpati Kota Semarang - Arifin, Siti Mirza Nuria; Malik, Abdul (Journal Of Human And Education (JAHE), 2024)
Women's empowerment is an effort to give power to women to develop their potential so that they can innovate to develop themselves. In this case, empowerment is needed to develop the role of women in the economic sector. One of the main activities is through the development of UMKM which can help women to be more empowered in improving the economy and improving their standard of living. This study aims to describe the process of women's empowerment through UMKM Mekarsari in Kandri Village and also related to the success of women's empowerment. This study uses qualitative descriptive research. The implementation technique is to collect data through observation, interviews and documentation. Data analysis uses an interactive data collection model, data reduction, data presentation and drawing conclusions. The results of the study obtained from the process of women's empowerment through UMKM Mekarsari through the Sarah Longwe stages which are as an analysis to determine the extent to which women have developed towards equality through 5 stages, namely the control stage, participation stage, critical awareness stage, access stage and stage in this welfare stage women already have levels and rights that are equal to men who are members of UMKM. The success of empowerment is obtained from intrinsic and extrinsic factors where there is support and facilities in the development skills of women that can be utilized for the development of the business being pursued